Revised intracerebral hemorrhage expansion definitions: Relationship with care limitations. Issue 6 (August 2021) - Lun, Ronda; Yogendrakumar, Vignan; Walker, Greg; Shamy, Michel; Fahed, Robert; Qureshi, Adnan; Dowlatshahi, Dar
Background: Hematoma expansion is an important therapeutic target in intracerebral hemorrhage. Recently proposed hematoma expansion definitions have not been validated, and no previous definition has accounted for withdrawal of care. Aims: To externally validate revised definitions of hematoma expansion that incorporate intraventricular hemorrhage, and to test their validity in the context of withdrawal of care. Methods: We analyzed data from the Antihypertensive Treatment of Acute Cerebral Hemorrhage II trial, comparing revised definitions of hematoma expansion incorporating intraventricular hemorrhage expansion to the conventional definition of "≥6 mL or ≥33%." Primary outcome was modified Rankin Scale of 4–6 at 90 days. We calculated the incidence, sensitivity, specificity, positive and negative predictive values, and c- statistic for all definitions of hematoma expansion. Definitions were compared using nonparametric methods. Secondary analyses were performed after removing patients with withdrawal of care. Results: Primary analysis included 948 patients. Using the conventional definition, the sensitivity was 37.1% and specificity was 83.2% for the primary outcome. Sensitivity improved with all three revised definitions (53.3%, 48.7%, and 45.3%, respectively), with minimal change to specificity (78.4%, 80.5%, and 81.0%, respectively). The greatest improvement was seen with the definition "≥6 mL or ≥33% or any intraventricular hemorrhage, " with increased c -statistic from 60.2% to 65.9% ( p  < 0.001). Secondary analysis excluded 46 participants who experienced withdrawal of care. The revised definitions similarly outperformed the conventional definition in this population, with the greatest improvement in c -statistic using "≥6 mL or ≥33% or any intraventricular hemorrhage" (58.1% vs. 64.1%, p  < 0.001). Conclusions: Revised hematoma expansion definitions incorporating intraventricular hemorrhage expansion outperformed conventional definitions for predicting poor outcome, even after accounting for care limitations.